2011
DOI: 10.1029/2011ja016914
|View full text |Cite
|
Sign up to set email alerts
|

Voyager observations of magnetic fields and cosmic rays in the heliosheath

Abstract: [1] The major features of the profile of >70 MeV/nuc cosmic ray intensity (CRI) observed by Voyager 1 (V1) in the heliosheath from 2005.8-2010.24 are described by the empirical "CR-B" relation as the cumulative effect of variations of the magnetic field strength B. The CRI profile observed by Voyager 2 (V2) from 2008.60 to 2010.28 in the heliosheath is also described by the CR-B relation. On a smaller scale, of the order of a hundred days, a sequence of 3 CRI decreases observed by V1 during 2006 was interprete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
17
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 30 publications
5
17
0
Order By: Relevance
“…The effects of a termination shock or heliosheath are not included in the present study. This is a limitation, in that observations and numerical simulations have shown that some modulation can occur within the heliosheath (see, e.g., Caballero-Lopez et al 2010;Burlaga et al 2011). The exclusion of effects due to the heliosheath is done for two reasons (Engelbrecht & Burger 2013), the first of which is that the Oughton et al (2011) was derived assuming an Alfvén speed considerably smaller than the solar wind speed, which is not the case in the heliosheath.…”
Section: Cosmic-ray Modulationmentioning
confidence: 99%
“…The effects of a termination shock or heliosheath are not included in the present study. This is a limitation, in that observations and numerical simulations have shown that some modulation can occur within the heliosheath (see, e.g., Caballero-Lopez et al 2010;Burlaga et al 2011). The exclusion of effects due to the heliosheath is done for two reasons (Engelbrecht & Burger 2013), the first of which is that the Oughton et al (2011) was derived assuming an Alfvén speed considerably smaller than the solar wind speed, which is not the case in the heliosheath.…”
Section: Cosmic-ray Modulationmentioning
confidence: 99%
“…The widths of all these current sheets, assumed to be nonpropagating, correspond to thicknesses of the order of 15-30 R L , similar to vales in the supersonic solar wind. Here R L , is the Larmor radius of the pickup ion dominated plasma in the heliosheath, where the characteristic temperature is 4.6 × 10 6 K and the average B is ≈ 0.1 nT [23].…”
Section: Discussionmentioning
confidence: 99%
“…A GMIR in the supersonic solar wind can be preceded by a strong shock, which results from the coalescence of many forward shocks produced by solar activity [Burlaga et al 2003]. An example of a GMIR produced in the heliosheath observed by V2 is shown in Figure 4 [Burlaga et al 2011] In this case, the magnetic field strength in the GMIR is twice that in the ambient heliosheath, and it moved past V2 during an interval of 40 days. There is an indication that the GMIR was preceded by a fast-forward shock, but this occurred in a data gao.…”
Section: Heliosheathmentioning
confidence: 99%
“…Such a cosmic ray profile is called a long-lasting Forbush decrease. The red curve and Figure 4b is derived from the CR-B relation [Burlaga et al 2011] that has been observed in the heliosphere that distances greater than or equal to 10 AU. Burlaga et al [1993] found that long-lasting Forbush decreases were associated with sustained enhanced solar activity for 1-3 solar rotations which introduce strong fields carried by coronal mass ejection and magnetic clouds as well as shocks associated with faster streams associated with these ejecta Burlaga et al [2003] showed that such activity could produce organized structures (expanding shells of disturbed magnetic fields and shocks) in the heliosphere at approximately 15 AU characterized by an interval of strong magnetic fields moving past V1 and V2 for 1-3 solar rotations, and persisting out to at least 90 AU.…”
Section: Heliosheathmentioning
confidence: 99%